TRIM21 mediates the synergistic effect of Olaparib and Sorafenib by degrading BRCA1 through ubiquitination in TNBC - Ning Huang; Peng Li; Xiaolin Sun; Li Tong; Xinyi Dong; Xuemei Zhang; Jifeng Duan; Xia Sheng; Hong Xin (npj Breast Cancer, 2023)
Abstract Triple-negative breast cancer (TNBC) is a heterogeneous and aggressive type of breast cancer with a poor prognosis and a high recurrence rate. Chemotherapy is still the mainstay of treatment for cancer patients without a genetic BRCA mutation, despite the approval of Olaparib, an inhibitor of the poly (ADP-ribose) polymerase (PARP) enzyme. Tripartite motif containing-21 (TRIM21) is one of the TRIM family members that has been investigated in various types of cancer. Here, we found that a low TRIM21 expression level was correlated with poor overall survival of TNBC patients. Knockout of TRIM21 promoted the proliferation of TNBC cells in vivo and in vitro, as well as migratory and invasive capabilities in vitro. Importantly, breast cancer susceptibility gene 1 (BRCA1) was identified as a ubiquitination substrate of TRIM21. It was confirmed that BRCA1 was upregulated after Olaparib treatment, which may explain the relative resistance of BRCA1-proficient TNBC cells to Olaparib. Moreover, Sorafenib, a standard treatment for hepatocellular carcinoma, increased the sensitivity of TNBC cells to Olaparib by promoting TRIM21-mediated ubiquitination degradation of BRCA1. Thus, a synergic effect of Olaparib and Sorafenib was found in vitro and in vivo. This combined treatment also aggravated DNA damage, cell cycle arrest, and apoptosis of TNBC cells. In summary, the findings verified the synergistic effect of Olaparib and Sorafenib and revealed TRIM21 as a potential target for TNBC therapy.